A CRITICAL REVIEW OF SECULARIZATION DEBATES: BRINGING IN THE QUESTION OF HUMAN AGENCY AND SOCIAL MOVEMENT DYNAMICS. - NİŞANCI, Zübeyir (Dîvân: Journal of Interdisciplinary Studies / Disiplinlerarasi Calismalar Dergisi, 2022)
This paper critically and comparatively reviews the basic assumptions of two most prominent secularization theories such as the secularization theory and the rational choice theory. Not denying practical values of their conceptual tools, this paper argues that these two theories fell short of providing (1) theoretically and methodologically well-grounded articulations (definitions) of religion and secularity and (2) systematic accounts of the role of social forces (collective action) primarily including social movement dynamics in their sociological studies of secularization. In order to address such limitations in the study of secularization, this paper proposes a new framework which combines two alternative perspectives presented by Christian Smith and Charles Taylor. Consequently, this paper argues that (1) secularization should be studied with reference to human agency and collective action, in other words, with regard to social movement dynamics and (2) that we need substantive definitions for the systematic study of secularism and religion which inquire into the philosophical dimensions of the two sides (secular and religious).